Status, composition and diversity of avifauna in the artificial Putrajaya Wetlands and comparison with its two neighboring habitats - Ismail, Ahmad; Abdul Rahman, Mohd Faid; Zulkifli, Syaizwan Zahmir (Chulalongkorn University Museum of Natural History, Department of Biology, Faculty of Science, Chulalongkorn University, 2012)
Current trends in landscaping, particularly of new townships, incorporates artificial habitat as one of its important features. In Malaysia, the newly developed Putrajaya city integrates an artificial wetland ecosystem to rehabilitate the water quality in the surrounding area. The habitat has attracted many bird species from local to migratory birds to roost, forage and nest in the area. This study evaluated the avifauna status, distribution and potential importance of the Putrajaya Wetlands to them. The avifauna distribution and status were found to vary across the different regions (each has a different habitat) of the wetlands. The northern area possessed the highest species diversity, richness and evenness compared to the other areas, which can be explained by the hydrology and human activity in the area. Comparison with the neighbouring protected habitats, one forest and one wetlands, showed that Putrajaya Wetlands has a far lower diversity of birds, both at the species and family levels, and a preponderance of generalist species, which is probably due to the fact that the wetlands’ ecosystem it still new and developing. Nevertheless, the presence of several overlapping species in this artificial habitat with the two neighbouring ones, including migratory species and mixed-species colonies, shows that the area has the potential to be an important link for neighbouring bird areas.